An Ameliorated Improvement Factor Model for Imperfect Maintenance and Its Goodness of Fit - Zhang, Mimi; Xie, Min (My University, 2017)
Maintenance actions can be classified, according to their efficiency, into three categories: perfect maintenance, imperfect maintenance, and minimal maintenance. To date, the literature on imperfect maintenance is voluminous, and many models have been developed to treat imperfect maintenance. Yet, there are two important problems in the community of maintenance that still remain wide open: how to give practical grounds for an imperfect-maintenance model, and how to test the fit of a real dataset to an imperfect-maintenance model. Motivated by these two pending problems, this work develops an imperfect-maintenance model by taking a physically meaningful approach. For the practical implementation of the developed model, we advance two methods, called QMI method and spacing-likelihood algorithm, to estimate involved unknown parameters. The two methods complete each other and are widely applicable. To offer a practical guide for testing fit to an imperfect-maintenance model, this work promotes a bootstrapping approach to approximating the distribution of a test statistic. The attractions and dilemmas of QMI method and spacing-likelihood algorithm are revealed via simulated data. The utility of the developed imperfect-maintenance model is evidenced via a real dataset. This article has a supplementary material online.
PUBLISHED
Keywords: Censored data; Maximum spacing estimation; Model selection; Parametric bootstrap; Quasi-Monte Carlo integration